Letters of the Repressed: the Literary Nature of the Bronius Sivickas’ Letters from Mordovia - Sivickaitė-Sadauskienė, Jurga (Tautosakos darbai, 2023)
The article aims at presenting and discussing letters of the political prisoner, pedagogue and writer Bronius Sivickas (1924–1991), sent home to Lithuania from the Mordovia prison camp. The surviving 47 letters, written in 1957–1958, constitute an eloquent document of the post-war years, revealing relevant details of the political prisoners’ life at the place of imprisonment, as well as their emotional state and cultural or spiritual interests. The article mainly focuses on the literary nature of these documents as a hitherto unexplored side of the deportees’ letters. Several features of this literary nature are discerned: 1) language and structure of the letters, 2) poetical insertions occurring in the letters, 3) references by the addressee to various literary works, quotations, and aphorisms that become rhetorical and value-related accents of the letters’ content. All these features are analyzed assuming that the literary elements of the letters may be related in part to the function of poetical therapy, which is relevant in case of the correspondence produced while living through traumatic experiences. The attention is also paid to the issues of the addressee’s sincerity, openness, and attitude, and his games with the censorship when attempting to find certain ideologically safe expressions.